1980
DOI: 10.1520/jfs12147j
|View full text |Cite
|
Sign up to set email alerts
|

Drug Identification Through Analysis of Maggots

Abstract: The examination of insect larvae from decomposed bodies not only can serve in the estimation of the postmortem interval but also can be used in qualitative identification of drug substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
6

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(47 citation statements)
references
References 0 publications
0
38
0
6
Order By: Relevance
“…Following the work of Beyer et al [9], demonstrating the presence of phenobarbital in larvae found on a skeletonised female body, numerous experiments were carried out by other groups [10,11,12,13,14,15,16,20,21,23,24] to detect controlled substances and drugs (e.g. opiates, benzodiazepines, antidepressants, cocaine, acetylsalicylic acid and amphetamine derivatives) and to gain useful information on the cause of death, when the toxicologist was unable to examine the usual biological fluids and tissues.…”
Section: Drugs In Larvaementioning
confidence: 99%
See 3 more Smart Citations
“…Following the work of Beyer et al [9], demonstrating the presence of phenobarbital in larvae found on a skeletonised female body, numerous experiments were carried out by other groups [10,11,12,13,14,15,16,20,21,23,24] to detect controlled substances and drugs (e.g. opiates, benzodiazepines, antidepressants, cocaine, acetylsalicylic acid and amphetamine derivatives) and to gain useful information on the cause of death, when the toxicologist was unable to examine the usual biological fluids and tissues.…”
Section: Drugs In Larvaementioning
confidence: 99%
“…An analytical technique similar to that for extraction of drugs from hairs is employed. Miller et al [20] described the first detection of drugs (amitriptyline) from chitinised insect tissues (puparial cases and exuviae), associated with mummiToxic drugs detected and reference Analytical findings Barbiturates: phenobarbital [9] Case report Analytical method: GC/MS Results: 100 µg/g…”
Section: Drugs In Puparial Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tal resultado evidencia uma influência significativa da testosterona no crescimento de larvas de C. albiceps. 6 e, atualmente, os insetos são uma alternativa confiável para análises toxicológicas, especialmente na ausência de tecidos e fluidos normalmente utilizados para esse propósito 5,7 . Em virtude disso, os dípteros e suas larvas que são encontrados em cadáveres podem contribuir consideravelmente para a identificação de substâncias exógenas presentes no corpo 8 , ciência conhecida como entomotoxicologia.…”
Section: Introductionunclassified